Water Treatment Chemicals
By using a water treatment agent containing a copolymer of specific structural units and a base pH adjuster, the problem of insufficient inhibition of silicate-based surface layer in the prior art is solved, and effective inhibition of silicates is achieved and prevention of their formation and accumulation.
Patent Information
- Application Number
- JP2020206537
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-14
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2040-12-14
AI Technical Summary
The prior art has shortcomings in the ability to inhibit the surface layer of silicates, especially in the fields of geothermal power plants, where the formation of silicates has caused great trouble to the equipment.
A water treatment agent is used that comprises a copolymer containing structural units from formic acid acetate, a sulfate group containing a salt group and an ether bond, and a base pH adjuster.
This water treatment agent significantly improves the ability to inhibit the surface layer of silicates, can effectively prevent the formation and accumulation of silicates, thereby extending the service life of the equipment.
Smart Images

Figure 0007657045000001 
Figure 0007657045000002 
Figure 0007657045000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a water treatment agent, and more particularly to a water treatment agent used to inhibit scale such as silica scale. [Background technology]
[0002] For example, the generation of scale such as calcium carbonate and silica is a problem in geothermal power generation, industrial cooling water, boiler water systems, wastewater treatment, seawater desalination, and the like.
[0003] For example, the copolymer described in Patent Document 1 improves the dispersibility of hydrophobic particles and also exhibits excellent chelating ability for calcium ions, making it possible to exhibit extremely good scale inhibition ability for the piping and inside of geothermal power generation equipment, and therefore it is disclosed that it can be suitably used as a scale inhibitor for geothermal power generation equipment. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-64382 A Summary of the Invention [Problem to be solved by the invention]
[0005] As mentioned above, various scale inhibitors have been proposed, but there has been a demand for further improvement in the silica scale inhibition ability. Therefore, an object of the present invention is to provide a water treatment agent that has superior silica scale inhibition capability compared to conventional agents and can therefore be suitably used, for example, as an inhibitor of silica scale. [Means for solving the problem]
[0006] The present inventors have conducted various investigations to achieve the above object and have arrived at the present invention. That is, the water treatment agent of the present disclosure is a water treatment agent that includes a copolymer including a structural unit derived from (meth)acrylic acid (salt), a structural unit derived from a monomer containing a sulfonic acid (salt) group, and a structural unit derived from a monomer containing an ether bond, and a basic pH adjuster. Effect of the Invention
[0007] The water treatment agent of the present disclosure exhibits good suppression ability of silica components, etc. Therefore, the water treatment agent of the present disclosure can be preferably used as a water treatment agent used for suppressing scale such as silica scale. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The present invention will be described in detail below. In addition, a combination of two or more of the individual preferred embodiments of the present invention described below is also a preferred embodiment of the present invention.
[0009] [Water treatment agent of the present disclosure] The water treatment agent of the present disclosure includes a copolymer including a structural unit derived from (meth)acrylic acid (salt), a structural unit derived from a monomer containing a sulfonic acid (salt) group, and a structural unit of a monomer containing an ether bond, and a basic pH adjuster. The above copolymer may be referred to as the copolymer of the present disclosure.
[0010] <Structural unit derived from (meth)acrylic acid (salt)> In this disclosure, (meth)acrylic acid refers to acrylic acid, methacrylic acid, and salts thereof. The above salt is not particularly limited, but examples thereof include alkali metal salts, alkaline earth metal salts, transition metal salts, and ammonium salts. In the present disclosure, the structural unit derived from (meth)acrylic acid (salt) refers to a structural unit in which the carbon-carbon double bond of (meth)acrylic acid (salt) is replaced with a carbon-carbon single bond. For example, if acrylic acid is CH2=CH(COOH), the structural unit derived from acrylic acid can be represented as -CH2-CH(COOH)-. The structural unit derived from (meth)acrylic acid (salt) can be formed, for example, by radical polymerization of (meth)acrylic acid (salt). Note that the structural unit derived from (meth)acrylic acid (salt) is not limited to a structural unit formed by polymerization of (meth)acrylic acid (salt), as long as it has the same structure as the structure in which the carbon-carbon double bond of (meth)acrylic acid (salt) is replaced with a carbon-carbon single bond, and may be, for example, a structural unit formed by a post-reaction after polymerization. The content of the structural unit derived from (meth)acrylic acid (salt) in the copolymer of the present disclosure is 15% by mass or more and 94% by mass or less, preferably 30% by mass or more and 89% by mass or less, more preferably 50% by mass or more and 85% by mass or less, based on 100% by mass of the structural units derived from all monomers constituting the copolymer of the present disclosure. The content of the structural unit derived from the (meth)acrylic acid (salt) is calculated in terms of (meth)acrylic acid. The term "in terms of (meth)acrylic acid" means that even if the structural unit derived from (meth)acrylic acid (salt) is a structural unit derived from a (meth)acrylic acid salt, the mass is calculated as (meth)acrylic acid. By being in the above range, the scale inhibitor of the present disclosure tends to have improved scale inhibition ability.
[0011] <Structural unit derived from monomer containing sulfonic acid (salt) group> In the present disclosure, a sulfonic acid (salt) group-containing monomer refers to a compound that contains at least one carbon-carbon double bond and a sulfonic acid (salt) group. The at least one carbon-carbon double bond is usually radically polymerizable. The above salt is not particularly limited, but examples thereof include alkali metal salts, alkaline earth metal salts, transition metal salts, and ammonium salts. In the present disclosure, the structural unit derived from a sulfonic acid (salt) group-containing monomer refers to a structural unit in which at least one carbon-carbon double bond of a sulfonic acid (salt) group-containing monomer is replaced with a carbon-carbon single bond. Note that the structural unit derived from a sulfonic acid (salt) group-containing monomer may have the same structure as the structure in which at least one carbon-carbon double bond of a sulfonic acid (salt) group-containing monomer is replaced with a carbon-carbon single bond, and is not limited to a structural unit formed by polymerization of a sulfonic acid (salt) group-containing monomer, and may be, for example, a structural unit formed by a post-reaction after polymerization. The content of the structural unit derived from the sulfonic acid (salt) group-containing monomer in the copolymer of the present disclosure is 5% by mass or more and 55% by mass or less, preferably 8% by mass or more and 45% by mass or less, more preferably 10% by mass or more and 30% by mass or less, based on 100% by mass of the structural units derived from all monomers constituting the copolymer of the present disclosure. The content of the structural unit derived from the sulfonic acid (salt) group-containing monomer is calculated in terms of sodium salt. The calculation in terms of sodium salt means that even if the sulfonic acid (salt) group contained in the structural unit derived from the sulfonic acid (salt) group-containing monomer is, for example, an acid-type sulfonic acid group, the mass is calculated as the sodium salt of the sulfonic acid group. By being in the above range, the scale inhibition ability of the scale inhibitor of the present disclosure tends to be improved.
[0012] Specific examples of sulfonic acid (salt) group-containing monomers include vinyl sulfonic acid and its salts, styrene sulfonic acid and its salts, (meth)allyl sulfonic acid and its salts, 3-(meth)allyloxy-2-hydroxypropanesulfonic acid and its salts, 3-(meth)allyloxy-1-hydroxypropanesulfonic acid (hereinafter also referred to as HAPS) and its salts, 2-(meth)allyloxyethylenesulfonic acid and its salts, 2-acrylamido-2-methylpropanesulfonic acid and its salts, etc. Since the scale inhibitor of the present disclosure tends to have improved scale inhibition ability, 3-(meth)allyloxy-2-hydroxypropanesulfonic acid and its salts are preferred, and 3-allyloxy-2-hydroxypropanesulfonic acid and its sodium salt are more preferred.
[0013] <Structural units derived from ether bond-containing monomers> In the present disclosure, the ether bond-containing monomer refers to a compound containing at least one carbon-carbon double bond and an ether bond. However, a sulfonic acid (salt) group-containing monomer is not included in the ether bond-containing monomer even if it is a compound containing an ether bond. The at least one carbon-carbon double bond is usually radically polymerizable. In the present disclosure, the structural unit derived from an ether bond-containing monomer refers to a structural unit in which at least one carbon-carbon double bond of an ether bond-containing monomer is replaced with a carbon-carbon single bond. Note that the structural unit derived from an ether bond-containing monomer may have the same structure as the structure in which at least one carbon-carbon double bond of an ether bond-containing monomer is replaced with a carbon-carbon single bond, and is not limited to a structural unit formed by polymerization of an ether bond-containing monomer, and may be, for example, a structural unit formed by a post-reaction after polymerization. The content of the structural unit derived from the ether bond-containing monomer in the copolymer of the present disclosure is 1% by mass or more and 30% by mass or less, preferably 3% by mass or more and 25% by mass or less, more preferably 3% by mass or more and 20% by mass or less, and most preferably 3% by mass or more and 15% by mass or less, based on 100% by mass of the structural units derived from all the monomers constituting the copolymer of the present disclosure. In addition, when the structural unit derived from the ether bond-containing monomer contains an acid group such as a carboxyl group (salt), the content is calculated in terms of acid. The term "acid equivalent" means that even when the structural unit derived from the monomer contains a salt of an acid group, the mass is calculated as the corresponding acid. The mass of the structural units derived from other monomers described later is calculated in the same manner. By being in the above range, the scale inhibition ability of the scale inhibitor of the present disclosure tends to be improved. Examples of ether bond-containing monomers include vinyl ethers such as ethyl vinyl ether, butyl vinyl ether, and benzyl vinyl ether; (meth)allyl ethers such as ethyl methallyl ether, butyl methallyl ether, and benzyl methallyl ether; and isoprenyl ethers such as ethyl isoprenyl ether, butyl isoprenyl ether, and benzyl isoprenyl ether. However, since there is a tendency in particular to improve the dispersibility of scale, a monomer represented by the following general formula (1) is preferred.
[0014] [ka] (In the above general formula (1), R 0 R represents a hydrogen atom or a methyl group. 1 represents a CH2 group, a CH2CH2 group, or a direct bond. X represents a hydroxyl group, a group represented by the following general formula (2), or a group represented by the following general formula (3). Y represents a hydroxyl group, a group represented by the following general formula (2), or a group represented by the following general formula (3). However, one of X and Y represents a hydroxyl group, and the other represents a group represented by the following general formula (2) or a group represented by the following general formula (3).
[0015] [ka] (In the above general formulas (2) and (3), R 2 are the same or different and each represents an alkylene group having 2 to 4 carbon atoms. n represents an oxyalkylene group (-OR 2 R is the average number of moles of 0 to 5. 3 , R 4 , R 5 each independently represents an alkyl group having 1 to 20 carbon atoms. Since the scale inhibition ability of the scale inhibitor of the present disclosure tends to be improved, R 3 , R 4 , R 5More preferably, the number of carbon atoms is 1 to 12, even more preferably 1 to 8, and most preferably 1 to 4. The alkyl group may be linear or branched, may contain a cyclic structure, and may have a substituent. Examples of the substituent include an alkoxy group, an aryl group, a hydroxyl group, a carboxy group, an amino group, and a heterocyclic group. When the alkyl group has a substituent, the number of the substituents may be one or more, and it is preferable that the alkyl group including the substituent has the above carbon number.
[0016] <Structural units derived from other monomers> The copolymer of the present disclosure may, if desired, have structural units derived from monomers other than (meth)acrylic acid (salt), structural units derived from sulfonic acid (salt) group-containing monomers, and structural units derived from ether bond-containing monomers (also referred to as structural units derived from other monomers). In the present disclosure, the structural unit derived from another monomer refers to a structural unit in which at least one carbon-carbon double bond of another monomer is replaced with a carbon-carbon single bond. Note that the structural unit derived from another monomer may have the same structure as the structure in which at least one carbon-carbon double bond of the other monomer is replaced with a carbon-carbon single bond, and is not limited to a structural unit formed by polymerization of the other monomer, and may be, for example, a structural unit formed by a post-reaction after polymerization. In the copolymer of the present disclosure, the content of structural units derived from other monomers is 0% by mass or more and 15% by mass or less, preferably 0% by mass or more and 10% by mass or less, and more preferably 0% by mass or more and 5% by mass or less, relative to 100% by mass of structural units derived from all monomers constituting the copolymer of the present disclosure. Examples of the other monomers include carboxyl group-containing monomers such as maleic acid, itaconic acid, and salts thereof; unsaturated alcohols such as (meth)allyl alcohol and isoprenol, and monomers obtained by adding alkylene oxides thereto; polyalkylene glycol chain-containing monomers such as (meth)acrylic acid esters of alkoxyalkylene glycols; vinyl aromatic monomers having heterocyclic aromatic hydrocarbon groups such as vinylpyridine and vinylimidazole; dialkylaminoalkyl (meth)acrylates such as dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate, and dimethylaminopropyl acrylate; dialkylaminoalkyl (meth)acrylamides such as dimethylaminoethyl acrylamide, dimethylaminoethyl methacrylamide, and dimethylaminopropyl acrylamide; allylamines such as diallyl alkylamines and diallyl dimethylamine; and quaternized products thereof. N-vinyl monomers such as N-vinyl formamide, N-vinyl acetamide, N-vinyl-N-methyl formamide, N-vinyl-N-methyl acetamide, and N-vinyl oxazolidone; amide monomers such as (meth)acrylamide, N,N-dimethyl acrylamide, N-isopropyl acrylamide, and t-butyl acrylamide; hydroxyl group-containing monomers such as (meth)allyl alcohol and isoprenol; (meth)acrylic acid alkyl ester monomers such as butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and dodecyl (meth)acrylate; (meth)acrylic acid hydroxyalkyl monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxyhexyl (meth)acrylate; vinyl aryl monomers such as styrene, indene, and vinyl aniline; isobutylene, vinyl acetate, and the like.
[0017] <Physical properties of the copolymer of the present disclosure> The copolymer of the present disclosure preferably has a weight average molecular weight (Mw) of 3000 or more and 200000 or less, more preferably 5000 or more and 100000 or less, even more preferably 7000 or more and 60000 or less, particularly preferably 8000 or more and 60000 or less, even more preferably 10000 or more and 60000 or less, and most preferably 10000 or more and 45000 or less. By being in the above range, the scale inhibitory ability of the scale inhibitor of the present disclosure tends to be further improved. The copolymer of the present disclosure contains one or more structural units derived from (meth)acrylic acid (salt), one or more structural units derived from a monomer containing a sulfonic acid (salt), and one or more structural units derived from an ether bond-containing monomer, and may contain one or more structural units derived from other monomers as necessary. The copolymer of the present disclosure may contain structural units derived from a polymerization initiator or a chain transfer agent, such as a hydroxyl group, a sulfonic acid (salt) group, or a hypophosphorous acid (salt) group, at the main chain end or the like. The copolymer of the present disclosure contains an acid group such as a carboxylic acid (salt) group or a sulfonic acid (salt) group, but the acid group of the copolymer of the present disclosure may be neutralized. The neutralization rate can be calculated, for example, by conventional acid-base titration.
[0018] <Method for producing the copolymer of the present disclosure> The method for producing the copolymer of the present disclosure is not particularly limited, but it is usually preferable to produce the copolymer by polymerizing structural units derived from (meth)acrylic acid (salt), a sulfonic acid (salt) group-containing monomer, and an ether bond-containing monomer, and, as necessary, other monomers. In the process of producing the copolymer of the present disclosure, a polymerization initiator is usually used. In the process of producing the copolymer of the present disclosure, it is preferable to use a polymerization solvent and a chain transfer agent. Examples of the chain transfer agent include hydrogen peroxide, hypophosphorous acid (salt) such as sodium hypophosphite, hydrogen sulfite (salt) such as sodium hydrogen sulfite, and mercapto compounds.
[0019] [pH adjuster of the present disclosure] The pH adjuster of the present disclosure is a component constituting a water treatment agent, and has a role of adjusting the pH of the agent to an appropriate value. By adjusting the pH of the agent to an appropriate value, it is effective in suppressing scale such as silica scale, and furthermore, by adjusting the pH of the water under actual use conditions to an appropriate range, it is effective in preventing corrosion. From the viewpoint of preventing scale and corrosion of piping, etc., the pH adjuster of the present disclosure is preferably basic, and any chemical substance exhibiting basicity can be used. Examples of chemical substances exhibiting basicity include inorganic substances such as hydroxides of alkali metals and alkaline earth metals, and organic compounds such as ammonium salts and amine salts. Among them, inorganic substances are preferred for reasons of ease of availability and price, and for example, sodium hydroxide, potassium hydroxide, calcium hydroxide, etc. are preferred, and for reasons of price, substances exhibiting strong basicity such as sodium hydroxide and potassium hydroxide are particularly preferred, and sodium hydroxide is particularly preferred.
[0020] [Water treatment agent of the present disclosure] The water treatment agent of the present disclosure essentially contains the copolymer of the present disclosure and the basic pH adjuster of the present disclosure. The content of the copolymer of the present disclosure in the water treatment agent of the present disclosure is preferably 1% by mass or more and 90% by mass or less, more preferably 1% by mass or more and 70% by mass or less, and most preferably 1% by mass or more and 60% by mass or less. The water treatment agent of the present disclosure may contain a solvent such as water, other scale inhibitors, preservatives, etc. The water treatment agent of the present disclosure preferably has a pH of 8.0 or more when it contains water, for reasons of improving anticorrosiveness and scale inhibition ability. By being in the above range, the anticorrosiveness of the piping is improved and the amount of metal ion components eluted into the service water is reduced, so that the scale inhibition ability of the water treatment agent of the present disclosure tends to be further improved.
[0021] [Water treatment method of the present disclosure] The water treatment method of the present disclosure is preferably a water treatment method using the copolymer of the present disclosure and the pH adjuster of the present disclosure in combination. The copolymer of the present disclosure and the pH adjuster of the present disclosure may be added simultaneously or separately. The copolymer of the present disclosure is preferably 20% by mass or more, more preferably 25% by mass or more, and particularly preferably 30% by mass or more, based on 100% by mass of the copolymer of the present disclosure and the pH adjuster in total. On the other hand, 95% by mass or less is preferable, 90% by mass or less is more preferable, and 80% by mass or less is even more preferable. By adding at this ratio, the scale inhibition ability tends to be improved in the water treatment of the present disclosure.
[0022] [Use of the water treatment chemicals disclosed herein] The water treatment chemicals disclosed herein can exhibit high performance in aqueous applications, and can be preferably used as scale inhibitors in geothermal power generation processes, oil well and gas well processes, seawater desalination processes or waste liquid concentration processes using forward osmosis or reverse osmosis membranes, boiler water circulation systems, cooling water circulation systems, and the like.
[0023] The water treatment agent of the present disclosure can be preferably used as a scale inhibitor for silica scale or calcium carbonate, for example. The water treatment chemicals of the present disclosure are preferably adjusted to contain 0.01 ppm or more and 20% or less, preferably 0.01 ppm or more and 10% or less, calculated as polymer, in the above-mentioned various types of water that are the target of scale prevention treatment. EXAMPLES
[0024] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass". <Weight average molecular weight measurement conditions (GPC)> Equipment: Tosoh Corporation HLC8320 Column: SHODEX Asahipak GF-310-HQ, Showa Denko Corporation; GF-710-HQ, GF-1G-7B Column temperature: 40℃ Flow rate: 0.5ml / min Calibration curve: Polyacrylic acid standard from American Polymer Standards Corporation Eluent: 0.1N sodium acetate
[0025] <Synthesis of Monomer (1)> In a 500 mL glass four-neck flask equipped with a reflux condenser and a stirrer (paddle blade), Charge 370.0 g of n-butyl alcohol and 4.27 g of pelletized sodium hydroxide. The mixture was heated to 60°C while stirring. Next, allyl glycidyl ether (hereinafter referred to as "AG") was added. E) was added over 30 minutes, and the reaction was then carried out for 5 hours. The solution was transferred to a 1,000 ml recovery flask, and the solvent was removed using a rotary evaporator. Add 200.0 g of 20% by weight sodium chloride solution to this, and then dilute this solution in 500 ml The mixture was transferred to a separating funnel, shaken well, and then left to stand until the layers were separated, and the lower layer was removed. The upper layer was transferred to a 300 ml recovery flask and the solvent was removed using a rotary evaporator. The salt was removed by filtration to obtain monomer (1).
[0026] <Synthesis Example 1> 184.1g of pure water and 0.0252g of Mohr's salt were charged into a 2000mL glass separable flask equipped with a reflux condenser and a stirrer (paddle blade), and the temperature was raised to 85°C while stirring to prepare a polymerization reaction system. Next, 400.0g of 80% acrylic acid aqueous solution (hereinafter also referred to as "80% AA"), 166.9g of 40% 3-(meth)allyloxy-1-hydroxypropanesulfonic acid aqueous solution (hereinafter also referred to as "40% HAPS"), 20.0g of monomer (1), 102.4g of 15% sodium persulfate aqueous solution (hereinafter also referred to as "15% NaPS"), and 22.2g of 35% sodium hydrogensulfite aqueous solution (hereinafter also referred to as "35% SBS") were dropped from separate nozzles into the polymerization reaction system maintained at 85°C under stirring. The drop time of each solution was 180 minutes for 80% AA, 120 minutes for 40% HAPS, 150 minutes for monomer (1), 200 minutes for 15% NaPS, and 175 minutes for 35% SBS. The drop speed of each solution was constant, and each solution was continuously dropped. After the drop of 80% AA was completed, the reaction solution was kept at 85°C (aged) for another 30 minutes to complete the polymerization. After the polymerization was completed, 298.2 g of 48% aqueous sodium hydroxide solution (manufactured by Kaname Yakuhin Co., Ltd.) was gradually dropped while stirring and cooling the polymerization reaction solution to neutralize it. In this way, a polymer aqueous solution (1) containing the polymer (1) of the present invention and having a solid content concentration of 41.7% was obtained. The weight average molecular weight of the polymer (1) was 31,000.
[0027] <Synthesis Example 2> In a 5,000 mL glass separable flask equipped with a reflux condenser and a stirrer (paddle blade), 600.1 g of pure water and 0.064 g of Mohr's salt were charged, and the temperature was raised to 85°C while stirring to prepare a polymerization reaction system. Next, 1070.0 g of 80% AA, 446.5 g of 40% HAPS, 53.5 g of monomer (1), 287.4 g of 15% NaPS, and 37.1 g of 35% SBS were dropped from separate nozzles into the polymerization reaction system maintained at 85°C under stirring. The drop times of each solution were 180 minutes for 80% AA, 120 minutes for 40% HAPS, 120 minutes for monomer (1), 210 minutes for 15% NaPS, and 170 minutes for 35% SBS. The drop speed of each solution was constant, and each solution was continuously dropped. After the dropwise addition of 15% NaPS was completed, the reaction solution was maintained (aged) at 85° C. for an additional 20 minutes to complete the polymerization. After the polymerization was completed, the polymerization reaction solution was stirred and allowed to cool, while 29.4 g of a 48% aqueous sodium hydroxide solution (manufactured by Kaname Yakuhin Co., Ltd.) was gradually added dropwise to neutralize the polymerization reaction solution. In this way, polymer (2) of the present invention having a solid content of 46.7% was obtained. The weight average molecular weight of polymer (2) was 36,600.
[0028] <Silica scale inhibition rate evaluation test> Sodium silicate aqueous solution: Add ion-exchanged water to 129 g of sodium metasilicate nonahydrate (manufactured by Aldrich) to make a total of 150 g. Magnesium sulfate aqueous solution: Add ion-exchanged water to 8.115 g of magnesium sulfate heptahydrate (manufactured by Wako Pharmaceutical Co., Ltd.) to make a total of 1000 g. Water treatment agent: 48% sodium hydroxide aqueous solution (Kaname Yakuhin Co., Ltd.) was diluted with ion-exchanged water to prepare 10% sodium hydroxide aqueous solution. A 10% sodium hydroxide aqueous solution and ion-exchanged water were added to the polymer aqueous solution obtained in the synthesis example as described in the examples. 2.3 g of the above water treatment agent diluted with ion-exchanged water to a polymer concentration of 1000 ppm, 32.4 g of deionized water, 2.8 g of the above sodium silicate aqueous solution, and 2.5 g of magnesium sulfate aqueous solution were mixed and placed in an oven at 70°C and left for 48 hours. The test liquid was then suction filtered using a filter with 0.45 μm openings, and the resulting filtrate was subjected to ICP (optical emission spectroscopy) to measure the Si concentration after the test in terms of SiO2. Silica scale inhibition rate (%) = SiO2 after test (ppm) / SiO2 concentration before test (ppm) x 100 The silica scale inhibition rate was judged according to the following criteria. <Inhibition rate evaluation criteria> 46% or more: Yes Less than 46%: ×
[0029] <Example 1> To 5.25 g of the polymer (1) obtained in Synthesis Example 1, 3.12 g of a 10% aqueous solution of sodium hydroxide (manufactured by Kaname Chemical Co., Ltd.) as a pH adjuster and 44 g of ion-exchanged water were added to obtain a water treatment agent with a pH of 9.0. This water treatment agent was further diluted with ion-exchanged water so that the polymer concentration became 1000 ppm, and a polymer-containing aqueous solution was obtained. When the silica scale inhibition rate evaluation test was carried out, the pH of the test liquid after being left for 48 hours was 11.2.
[0030] <Example 2> To 3.8 g of the polymer (2) obtained in Synthesis Example 2, 7.9 g of a 10% aqueous sodium hydroxide solution as a pH adjuster and 27 g of ion-exchanged water were added to obtain a water treatment agent with a pH of 9.2. A silica scale inhibition rate evaluation test was carried out in the same manner as in Example 1. The solution pH after the test was 11.2.
[0031] <Comparative Example 1> A water treatment agent having a pH of 5.5 was obtained by adding 56.9 g of ion-exchanged water to 5.2 g of the polymer (1) obtained in Synthesis Example 1. A silica scale inhibition rate evaluation test was carried out in the same manner as in Example 1. The pH of the solution after the test was 11.1. The results are shown in Table 1.
[0032] [Table 1] In Table 1, "composition" represents "structural units derived from acrylic acid (salt) / structural units derived from sodium 3-allyloxy-2-hydroxypropanesulfonate (HAPS) / structural units derived from monomer (1)." The results in Table 1 show that the water treatment agent of the present disclosure has excellent silica scale inhibition ability.
Claims
1. A copolymer including a structural unit derived from (meth)acrylic acid (salt), a structural unit derived from a sulfonic acid (salt) group-containing monomer, and a structural unit derived from an ether bond-containing monomer, and a basic pH adjuster, the pH being 8 or higher; The water treatment agent, wherein the structural unit derived from the ether bond-containing monomer is a structural unit derived from a monomer represented by the following general formula (1): 【Chemistry 1】 (In the general formula (1), R 0 represents a hydrogen atom or a methyl group. 1 is CH 2 Group, CH 2 CH 2 X represents a hydroxyl group, a group represented by the following general formula (2), or a group represented by the following general formula (3). Y represents a hydroxyl group, a group represented by the following general formula (2), or a group represented by the following general formula (3). However, one of X and Y represents a hydroxyl group, and the other represents a group represented by the following general formula (2) or a group represented by the following general formula (3). 【Chemistry 2】 (In the above general formulas (2) and (3), R 2 are the same or different and represent an alkylene group having 2 to 4 carbon atoms. n is an oxyalkylene group (-O-R 2 R is the average number of moles added of (-) and represents 0. 3 , R 4 , R 5 each independently represents an alkyl group having 1 to 20 carbon atoms.
2. 2. The water treatment agent according to claim 1, wherein the content of the structural unit derived from the ether bond-containing monomer in the copolymer is 1 mass% or more and 30 mass% or less, based on 100 mass% of the structural units derived from all monomers constituting the copolymer.
3. 3. The water treatment agent according to claim 1, wherein the content of the structural unit derived from the sulfonic acid (salt) group-containing monomer in the copolymer is 5% by mass or more and 55% by mass or less, based on 100% by mass of the structural units derived from all the monomers constituting the copolymer.
4. The water treatment agent according to any one of claims 1 to 3, wherein the weight average molecular weight of the copolymer is 3,000 or more and 200,000 or less.
5. The water treatment agent according to any one of claims 1 to 4, wherein the structural unit derived from a sulfonic acid (salt) group-containing monomer is a structural unit derived from 3-allyloxy-2-hydroxypropanesulfonic acid or a salt thereof.
6. A method for preventing scale adhesion, comprising using the water treatment agent according to any one of claims 1 to 5 for water treatment.
Citation Information
Patent Citations
Carboxyl / sulfone / polyalkylene oxide polymer used in suppressing precipitation of scale, corrosion and iron oxide
JP1986114797A
Treatment method of cooling water system
JP2013212435A
Treatment method for cooling water system
JP2014074196A
Scale inhibitor for geothermal power generation
JP2016064382A
Scale inhibitor for geothermal power generation devices, and scale prevention method for geothermal water
JP2018030088A